Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1159/000224798
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide-Triggered Acute Aggravation of Mesangioproliferative Glomerulonephritis through Activation of Coagulation in a High IgA Strain of ddY Mice

Abstract: Background: The high IgA (HIGA) strain of ddY mice represents an inbred model of IgA nephropathy that shows mesangioproliferative glomerulonephritis with mesangial IgA deposition. In this study, aggravation of glomerulonephritis in HIGA mice through lipopolysaccharide (LPS)-triggered activation of coagulation was investigated. Methods: Twelve-week-old HIGA and BALB/c mice were intraperitoneally injected with LPS twice at an interval of 3 days, and kidney specimens were collected 7 days after the second LPS inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 94 publications
0
5
0
Order By: Relevance
“…7 As the marker of gram negative bacterial infections, lipopolysaccharide (LPS) could trigger an acute aggravation of mesangioproliferative glomerulonephritis, induce experimental IgAN, and suppress C1GALT1C1 expression in patients with IgAN. [8][9][10] Therefore, this study was designed to determine whether LPS could induce aberrant IgA1 O-glycosylation by suppressing C1GALT1C1 expres-sion.…”
mentioning
confidence: 99%
“…7 As the marker of gram negative bacterial infections, lipopolysaccharide (LPS) could trigger an acute aggravation of mesangioproliferative glomerulonephritis, induce experimental IgAN, and suppress C1GALT1C1 expression in patients with IgAN. [8][9][10] Therefore, this study was designed to determine whether LPS could induce aberrant IgA1 O-glycosylation by suppressing C1GALT1C1 expres-sion.…”
mentioning
confidence: 99%
“…Human serum IgA has both pro-inflammatory and anti-inflammatory properties in LPS-stimulated monocytes and peripheral blood mononuclear cells 18,19. Shimosawa, et al20 reported that mesangial TLR4 expression decreased after LPS administration in a high IgA strain of ddY mice, while mesangial proliferation, macrophage infiltration, and MCP-1 mRNA expression increased. The modified mesangial responses to LPS and IgA observed in our study might contribute to the feedback mechanisms maintaining a balance between pro-inflammatory and anti-inflammatory activities.…”
Section: Discussionmentioning
confidence: 99%
“…For example, vascular leakage is a hallmark of sepsis or noninfectious tissue injury, because PAMPs increase vascular permeability by activating TLRs on vascular endothelial cells. 60,61 The same mechanism enhances proteinuria during immune complex glomerulonephritis as shown for systemic LPS exposure from Gram-negative bacteria 11,62,63 or lipoprotein from Gram-positive bacteria. 63 These bacterial cell wall components enhance the permeability of glomerular endothelial cell and podocyte monolayers by activating surface TLR2 and TLR4.…”
Section: How Infections Can Trigger Flares Of Autoimmune Kidney Diseasementioning
confidence: 91%